Re-Layout Layout of Material Warehouse Using Dedicated Storage Method at PT. A B C - R. Erik Hidayat; Boy Isma Putra (Universitas Muhammadiyah Sidoarjo, 2019)
PT. ABC is one of the companies that consentration in steel construction. The company has an extensive warehouse perfectly adequate. But the problems faced by PT. ABC in warehouse goods product company has no arrangements regarding the layout of raw materials, so at this time to adjust the position of the storage and preparation of raw materials, made by placing the material in an irregular position and randomly depending on the position of the empty warehouse. As a result, the time period of materials so long and the production becomes inhibited. The method used in this research is by using methods dedicated storage. This method is used to minimize time and comparing the activity mileage outgoing or incoming raw materials. From the analysis results obtained value is 8258.77 meter distance. Recommendations for improvement given that create a new layout for the arrangement of raw materials in PT. A B C